Genetics of two marine shrimp hatcheries of the Pacific white shrimp Litopenaeus vannamei (Boone, 1931) in Pernambuco, Brazil - Lima,Ana Patrícia Souza de (2010)
The shrimp industry has grown significantly over the past 10 years in Brazil, especially the farmed production of the exotic Pacific white shrimp, Litopenaeus vannamei. In 2004, this industry was marked by a productivity crisis, which stirred interest towards genetic improvement of shrimp stocks. Shrimp breeders importation was banned in Brazil by a govern Normative Instruction in 1997, as a sanitary precaution. Since then, broodstock replacement in hatcheries has been based on domestic stocks, raising concerns on the decline of genetic diversity and if the existing diversity would allow effective genetic improvement programs. In the present research, genetic parameters such as number of alleles, effective allele number, expected and observed heterozygosities, inbreeding coefficient, genetic differentiation index and deviation from Hardy-Weinberg equilibrium have estimated of two important commercial hatcheries in Northeast Brazil, genotyping 5 microsatellite loci. Effective allele number (3 to 10.5) and average observed and expected heterozygosities (0.480 and 0.680) were consistent with those reported for cultured and wild Penaeid populations. However, F IS positive values (0.381 for hatchery A and 0.249 for hatchery B) reflected a significant heterozygous deficiency within hatcheries (P<0.01). Nevertheless, we concluded that even after ten years of limited genetic input, it has been possible to maintain a high level of genetic variability, possibly due to the wide diverse origin of the founder broodstocks and the constant breeders exchange among hatcheries.